Inside Austronesian houses : perspectives on domestic designs for living - Fox, James J., 1940- (Comparative Austronesian series, 2006)
"The eight papers in this volume examine the spatial organization of a variety of Austronesian houses and relate the domestic design of these houses to the social and ritual practices of the specific groups who reside within them. The houses considered in this volume range from longhouses in Borneo to the meeting-houses of the Maori of New Zealand and from the magnificent houses of the Minangkabau of Sumatra to the simpler dwellings of the population of Goodenough Island in Papua New Guinea. Together these papers indicate common features of domestic design from island South-East Asia to Melanesia and the Pacific"--